(untitled) (Journal of Hama University, 2024)
This research aims to study the relationship between the internal records system and customer loyalty in Syria International Islamic Bank. The descriptive approach was followed, and the primary data was collected through a structured questionnaire that was distributed to the concerned employees of the Syrian International Islamic Bank. The internal records system in customer loyalty, and the results reveal that the internal records system in Syria International Islamic Bank enjoys high approval, which indicates its effectiveness. In addition, the study showed a good level of customer loyalty within the bank.